2021
DOI: 10.1080/21678421.2020.1867180
|View full text |Cite
|
Sign up to set email alerts
|

Problem-focused coping underlying lower caregiver burden in ALS-FTD: implications for caregiver intervention

Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is a multisystem neurodegenerative disorder which includes cognitive and behavioural symptoms akin to frontotemporal dementia (FTD).Despite the necessity of caregiver intervention to assist with the management of cognitive and behavioural symptoms, there has been a lack of research on the topic. A focus on caregiver coping may offer a promising foundation to guide the development of interventions as part of ALS care. Accordingly, the aim of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The sense of distance that can occur between people when communicating through social media can furthermore for some people enable particular forms of computer-mediated distal empathy and still enable interactions and sharing of experiences with peers [ 40 ]. However, timely provision of problem-solving coping strategies is important to take into account when mitigating caregiver burden in PALS/Cis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sense of distance that can occur between people when communicating through social media can furthermore for some people enable particular forms of computer-mediated distal empathy and still enable interactions and sharing of experiences with peers [ 40 ]. However, timely provision of problem-solving coping strategies is important to take into account when mitigating caregiver burden in PALS/Cis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that targeting information on cognitive and behavioral impairments not only offered an intimate and reflexive environment but was also useful to emphasize the shared destinies and to learn from peers. Caga et al (2021) also found it particularly important to offer information on ALS and cognitive impairments and problem-solving strategies as part of supporting caregivers of PALS/Cis [ 1 ]. Our results showed that some participants found it beneficial to keep a diary during the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations